If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -13 = 23 Reorder the terms: -13 + 2m = 23 Solving -13 + 2m = 23 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 2m = 23 + 13 Combine like terms: -13 + 13 = 0 0 + 2m = 23 + 13 2m = 23 + 13 Combine like terms: 23 + 13 = 36 2m = 36 Divide each side by '2'. m = 18 Simplifying m = 18
| 10.9-0.6p+1.1-1.5p=9-2.1p-5.4 | | 3d-12=-6 | | 8*9-4*6= | | 3-7(7-7x)=0 | | 8x-20=4-4x | | k-3=12 | | g(12+g)-9g-17= | | d/-3+2=5 | | -7+12x^2=0 | | 22+5h+h-15=8h+15-2h-8 | | 3-4(2x+9)=8 | | k-2=12 | | 6/x=3 | | a+1.6=2.1 | | 1.5(b+6)-(6.9+0.5b)=-9+7 | | n/7=-20 | | .33x-5=-3 | | 81x+1=12x | | 350m+3y=185 | | -77=7b | | -3(x+2)=-8(3x-8) | | 6(-7x+8)=48 | | 350m+3d=185 | | 2x*(x+10)=140 | | -3(x+3)-27=-11-7 | | 11=y+7 | | 11x-6x=-5 | | 120000=2.32n+34180 | | rad(x+10)=2+rad(x-6) | | 8x+10x=3 | | 2(x-8)=-11-1 | | 6(x-13)=39 |